An uncommon case of upper limb pterygia - Avinash Deodhar (Indian Journal of Plastic Surgery)
Reporting images in a case of a 9-year-old boy who presented with bilateral congenital webbing (pterygium) of axillae and elbows. This deformity was restricting his axilla and elbow movements. This was successfully treated on one side with multiple Z-plasty. An outline of multiple pterygium syndrome is given herewith.